Rested-Baseline Responsivity of the Ventral Striatum Is Associated With Caloric and Macronutrient Intake During One Night of Sleep Deprivation - Satterfield, Brieann C.; Raikes, Adam C.; Killgore, William D. S. (Frontiers in Psychiatry, 2019)
Background: Sleep loss contributes to obesity through a variety of mechanisms, including neuroendocrine functioning, increased hunger, and increased food intake. Additionally, sleep loss alters functional activation within brain regions associated with reward and behavioral control. However, it remains unknown whether individual differences in baseline neural functioning can predict eating behaviors during total sleep deprivation (TSD). We used functional magnetic resonance imaging (fMRI) to test the hypothesis that individuals with increased baseline responsiveness within reward regions are more vulnerable to TSD-induced overeating. Methods: N=45 subjects completed several fMRI scans during a single pre-TSD session that included performance on the Multi-Source Interference Task (MSIT) and the n-back task. Subjects returned to the laboratory for an overnight TSD session, during which they were given ad libitum access to 10,900 kcal of food. Leftover food and packaging were collected every 6 hours (00:00, 06:00, 12:00) to measure total food consumption. Subjects reported sleepiness every hour and performed a food rating task every 3 hours. Results: Functional activation within the ventral striatum during the MSIT and n-back was positively correlated with total caloric and carbohydrate intake during the final 6 hours (06:00–12:00) of TSD. Activation within the middle and superior temporal gyri during the MSIT also correlated with total carbohydrates consumed. Food consumption was not correlated with subjective sleepiness, hunger, or food desire. Conclusions: Individual differences in neural activity of reward processing areas (i.e., nucleus accumbens) prior to sleep deprivation is associated with an individual’s propensity to overeat during subsequent sleep deprivation. This suggests that individual differences within reward processing pathways are potential key factors in sleep loss related overeating. Sleep loss and obesity are tightly linked. Both phenomena have been associated with increased neural activation in regions associated with reward, inhibitory control, and disrupted dopamine signaling. Elevated baseline reward sensitivity in the ventral striatum appears to be further compounded by sleep deprivation induced dysfunction in the reward neurocircuitry, increasing the likelihood of overeating. Our findings suggest that large individual differences in baseline responsiveness of hedonic reward pathways may modulate the association between sleep loss and obesity.